The Medieval Chronicle 16
1 online resource (320 pages)
Keywords: Alongside annals, chronicles were the main genre of historical writing in the Middle Ages. All chronicles raise such questions as by whom, for whom, or for what purpose they were written, how they reconstruct the past, or which literary influences are discernible in them. Their significance as sources for the study of history, literature, linguistics, and art is widely appreciated. The series The Medieval Chronicle , published in cooperation with the Medieval Chronicle Society (medievalchronicle.org), provides a representative survey of on-going research in the field of chronicle studies, illustrated by examples from a wide variety of countries, periods, and cultural backgrounds.